Physico-Chemical quality analysis of drinking water samples in Darbandikhan region, Iraq - Muhammad, Muhammad Tahir; Ahmad, Parwa Rostam (International Journal of Psychosocial Rehabilitation, 2020)
From all natural resources in the earth, water is the most important for all living organisms. The aim of this study was to overview the quality of drinking water in a certain part of Darbandikhan, Iraq to secure the safe and clean of drinking water for protecting public health and conservation. In this study, we measure the physio-chemical properties and investigate drinking water for human utilization. Physio-chemical analysis encompass a number of parameters, such as color, odor, taste, temperature, PH, electro conductivity (EC), total dissolved solids (TDS), total chlorine, Alkalinity, Calcium, nitrate, potassium, and iron. These data were collected from 4 July 2018 – 9 Oct 2018. The attained rate of each of the parameters was compared with the standard values of the World Health Organization (WHO) and National Drinking Water Quality Standard (NDWQS). The water took from the locations was found to be safe and clean as a drinking water. The results demonstrated that the drinking water was assembled from different places in Darbandikhan region.